FAKTOR-FAKTOR YANG MEMPENGARUHI PENYERAPAN ANGGARAN PENDAPATAN DAN BELANJA DAERAH (APBD) PEMERINTAH KABUPATEN PASAMAN - Safpremi, Yolla; Putri, Annie Mustika; Ahyaruddin, Muhammad (Balance : Jurnal Akuntansi dan Bisnis, 2022)
This study aims to determine the influence of the factors that influence the absorption of the budget in the Pasaman Regency Government. The population in this study were all Regional Apparatus Organizations in the Pasaman Regency Government which consisted of 40 OPD. Sources of data used in this study is primary data and data collection is done directly by using a questionnaire. The research method used is a quantitative method with multiple linear regression analysis. The variables in this study consisted of 3 independent variables (independent) and the dependent variable (dependent). The 3 independent variables are the quality of human resources (X1), budget planning (X2), and procurement of goods and services (X3), while the dependent variable is budget absorption (Y). The results of this study indicate that partially the quality of human resources, budget planning, and procurement of goods/services has a positive and significant effect on the absorption of the Pasaman Regency Government's budget.